DESIGN OF DATA ACQUISITION FOR THE PRODUCTION AND UTILIZATION OF 500kWP SOLAR POWER PLANT AT CAMPUS-II ITN MALANG USING SCADA HAIWELL SOFTWARE - Muljanto, Widodo Pudji; Priyanto, Sugeng; Salam, Muhammad Farhan; Budi Sulistiawati, Irrine (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2023)
Monitoring or data acquisition is defined as monitoring or tracking activities. The existence of a 500Kwp solar power plant at Campus-II ITN Malang in 2021 requires monitoring of its production in real time. So far, data has been collected manually and generally only if further analysis is to be carried out. Data monitoring is observed locally at the monitoring terminal and does not yet provide system-specific data in real time. This research conducts periodic monitoring to determine the production power of a solar power plant in real time, accurately and specifically. The design of the tool consisting of hardware design (Toky DS9L series 3 phase power meter, USR-DR302) and software (Scada Haiwell) is used for online monitoring using the Modbus TCP/IP protocol with RS-485 to Ethernet. This system configuration provides the results of displaying the parameters of current, voltage, power, energy (Kwh) from the production of solar power plants as measured by a power meter and displayed on the Scada Haiwell dashboard.